Impact of adverse events of bevacizumab on survival outcomes of patients with recurrent glioblastoma. (April 2020) - Kamiya-Matsuoka, Carlos; Hamza, Mohamed A.; de Groot, John F.
Highlights: Bevacizumab is widely used for treatment of recurrent glioblastoma (rGB). Patients who discontinued bevacizumab because of AEs progressed earlier. Development of AEs to bevacizumab is associated with unfavorable survival outcomes. Abstract: Background: Bevacizumab is widely used for treatment of recurrent glioblastoma (rGB). It is well known that adverse events (AEs) due to bevacizumab can cause early discontinuation of treatment. However, the association between AEs and survival outcomes is not well defined. Methods: We retrospectively identified patients with rGB, who were treated with single-agent bevacizumab or bevacizumab-based combination regimens from 07/2005 through 07/2014, and who discontinued bevacizumab due to either AEs or physician's decision. Those who discontinued bevacizumab because of tumor progression were excluded. Demographic, treatment, and survival data were collected from the database. Results: Of 298 adults with rGB treated with bevacizumab in our database, 65 patients discontinued bevacizumab due to AEs (n = 39, 60%) or physician's decision (n = 26, 40%). There were no statistically significant differences in regards to age, performance status, extent of resection, number of lesions, the time between diagnosis and first recurrence, time between diagnosis and initiation of bevacizumab, number of recurrences before bevacizumab initiation, and duration of bevacizumab treatment between the two groups. Interestingly, patients who discontinued bevacizumab because of AEs progressed earlier after bevacizumab discontinuation (3.9 months vs 5.7 months; p = 0.02), had significantly shorter progression-free survival (PFS) (10.4 months vs 14.2 months; p = 0.01) and shorter overall survival (OS) from bevacizumab initiation (13.9 months vs 32.5 months; p = 0.01) as well as shorter OS from tumor diagnosis (20 months vs 49.3 months; p = 0.007) when compared to patients who discontinued bevacizumab due to a physician's decision. Conclusions: Our results indicate that the development of AEs to bevacizumab or bevacizumab-containing regimens is associated with unfavorable glioma-related survival outcomes in patients with rGB.